SAMIRATA a Musical Art Composition Creative Percusion | SAMIRATA Sebuah Karya Komposisi Seni Karawitan Tabuh Kreasi - Kadek Angga Wahyu Pradana; I Ketut Garwa (GHURNITA: Jurnal Seni Karawitan, 2021)
Abstract The creation of this final percussion is starting to decrease, especially in Buleleng. In the past five (5) years, there has been no creative percussion in the form of a game pattern that focuses on the melodic processing approach, but the packaging or presentation of creative percussion works tends to use a rhythmic working approach. From the differences above, the stylist wants to create a more dynamic musical composition work. The medium expressed in this creative musical composition is the North Balinese style barungan gong kebyar (pacekan). From this, ideas emerged in the stylist to create a creative percussion composition entitled "Samirata". "Samirata" can be divided into 2 words namely sami and rata. Sami which means all while flat which means the same high / low surface that covers all parts and gets the same amount. So, Samirata means something that is indicated by the same thing without any difference in number, in the whole part. The stylist imagines by systematically arranging a composition whose source of inspiration is from the similarities in various types of ornamentation in the techniques of ubitan gangsa maker, gangsa kantilan, reong with other instruments. Keywords: Samirata, Gong Kebyar, Ubit-ubitan, Equation.